Factors Related to Burnout in The Covid-19 Vaccination Team in Subang District 2020-2022: Faktor Faktor yang Berhubungan dengan Burnout pada Tim Vaksinasi COVID-19 di Kabupaten Subang 2020-2022 - Muhamad Azhari Maulana; Marsen Isbayuputra; Endang Parahyanti; Dewi S. Soemarko; Yudiana Ratnasari (The Indonesian Journal of Community and Occupational Medicine, 2022)
Introduction: The COVID-19 Pandemic was happening around the World, including in Indonesia. All sectors were impacted, including health workers. The risks for physical and mental health increased during the Pandemic, including Burnout. Vaccination was a method for giving humans immunity. Subang is a District, West Jawa, Indonesia with a government policy for accelerating vaccination, which may impact demand and increase the team’s Burnout potential.Aim: Research was conducted to detect what factors correlated with Burnout in the Vaccination Team in Subang.  Methods: Research was conducted in May – July 2022 in the Public Health Care, Subang District, West Java, Indonesia. The reseach uses simple random sampling, comprising 131 Vaccination Team members who complete this research. Variable factors are demographic factors (age, sex, marital status, education status), work factors (distance to workplace, work period, and task on the Vaccination Team), mental workload, and work locus of control. The analysis will be conducted with chi-square for correlation (bivariate) and logistic regression for analize the most related factors (multivariate). Result and Discussions: In this research, there is 44(33,3%) person of team members who have Burnout. No demographic factors correlate with Burnout (p-value>0.05). There is correlation between work period (p-value=0.022), mental workload (p-value = 0.049) and work locus of control (p-value=0.022) to Burnout. Work locus of control (p-value=0.012) was the most related factor to Burnout (aOR=2,9).Conclusion: Work period, mental workload, and locus control factors correlate with Burnout. Work locus of control was most related to Burnout in the Vaccination Team in the Subang District.